Improving Energy Efficiency in Sulfuric Acid Production from Sulfur and Air by Adding Heat Exchanger and Reducing Cooler - Andini, Dian Putri; Santoso, Lasya Fauziah; Bersa, Syifa Putri (Journal of Chemical Engineering Research Progress, 2025)
Sulfuric acid is a strong mineral acid and is useful for processing mineral ores, chemical synthesis, waste water processing, and others. The increasing need for sulfuric acid is not balanced with the amount of sulfuric acid production due to the use of quite a lot of energy in the production process. Therefore, innovation is being carried out, namely energy efficiency in sulfuric acid production from sulfur and air, which is expected to help increase production of sulfuric acid so that it can meet market needs. The sulfuric acid production process uses a contact process which is carried out with 3 reaction stages where the raw materials in the form of sulfur and free air are reacted in the reactor and SO2 gas is obtained, then SO2 reacts with oxygen to form SO3 gas in the converter bed, and finally the formation of H2SO4 from the reaction between SO3 and water in the absorber column. Modifications were made using Aspen HYSYS to improve energy efficiency in the sulfuric acid production. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).